Who will push my wheelchair? Choosing a family eldercare provider - Sofia Cristina Iost Pavarini; Fernanda Lopes Tonon; Jeniffer Marcela Carlos Silva; Marisa Zazzetta de Mendiondo; Elizabeth Joan Barham; Carmen Lúcia Alves Filizola (Universidade Federal de Goias, 2006)
The emotional ties and personal relationships we form during our lives affect the quality of our family relationships when we grow older. The objective of this study was to evaluate family functioning among elderly people attending adult literacy classes and to identify who they would choose to care for them in their older age. It was a descriptive and transverse study, based on the principles of the quantitative and qualitative research method. To the family functioning assessment, it was used the Family Apgar, proposed by SMILKSTEIN (1978) and data were statistically analyzed in frequency measures. 93 elderly people were evaluated. To the comprehension of caregiver choice it was made in-depth interviews with 9 participants, three of them from each Apgar category. Interviews were analyzed, following the Content Analyze Model, Thematic Analyze Category, proposed by BARDIN (1977). Ethical guidelines for research with human participants were followed. Results obtained with the Family Apgar Scale indicate that 81 participants were from well functioning families, 8 presented moderate family dysfunction and 4 presented high family dysfunction. In-depth interviews were conducted with three participants from each category. In all three groups, the caregiver of choice was the same with respect to: gender (female), family relationship (daughter) and family composition (multigenerational). The definition of "Who will push my wheelchair" is a choice determined by socio-cultural values and individual life histories; the choice is a multivariate issue, affected by lifelong processes.